An evidence gap map on Made in Africa Evaluation approaches: Exploration of the achievements - Tebogo E. Fish (African Evaluation Journal, 2022)
Background: The Made in Africa Evaluation (MAE) agenda is an effort at decolonising and indigenising evaluation practice in Africa. This involves developing new evaluation practices, theories, approaches and methodologies originating from African cultures, worldviews, knowledge systems, philosophies and African paradigms.